Engineering muscle tissue for the fetus: getting ready for a strong life - Christ, George J.; Siriwardane, Mevan L.; de Coppi, Paolo (Frontiers in Pharmacology, 2015)
Congenital malformations frequently involve either skeletal, smooth or cardiac tissues. When large parts of those tissues are damaged, the repair of the malformations is challenged by the fact that so much autologous tissue is missing. Current treatments require the use of prostheses or other therapies and are associated with a significant morbidity and mortality. Nonetheless, affected children have generally good survival rates and mostly normal schooling. As such, new therapeutic modalities need to represent significant improvements with clear safety profiles. Regenerative medicine and tissue engineering technologies have the potential to dramatically improve the treatment of any disease or disorder involving a lack of viable tissue. With respect to congenital soft tissue anomalies, the development of, for example, implantable muscle constructs would provide not only the usual desired elasticity and contractile proprieties, but should also be able to grow with the fetus and/or in the postnatal life. Such an approach would eliminate the need for multiple surgeries. However, the more widespread clinical applications of regenerative medicine and tissue engineering technologies require identification of the optimal indications, as well as further elucidation of the precise mechanisms and best methods (cells, scaffolds/biomaterials) for achieving large functional tissue regeneration in those clinical indications. In short, despite some amazing scientific progress, significant safety and efficacy hurdles remain. However, the rapid preclinical advances in the field bode well for future applications. As such, translational researchers and clinicians alike need be informed and prepared to utilize these new techniques for the benefit of their patients, as soon as they are available. To this end, we review herein, the clinical need(s), potential applications, and the relevant preclinical studies that are currently guiding the field toward novel therapeutics.